EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN BUAH NAGA (DRAGON FRUIT) DI KECAMATAN BATANG ANAI, KECAMATAN ULAKAN TAPAKIS DAN KECAMATAN NAN SABARIS KABUPATEN PADANG PARIAMAN - Widya Oktavia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
This Research aims to knowing and analysing about: The level of suitability areas, the diffusive spasial suitability, The guidance arrangement areas SIG – basis of areas for dragon fruit in Batang Anai, Nan Sabaris, Ulakan Tapakis district of Padang Pariaman Regency. The type of research used was Ex Post Facto. The technique of taking the sample is purposive sampling based on taken pointing one unit of area. There were 22 samples for this research. They were : 1)The area shaped of fluvial process, 2)The area shaped of marin procces, 3)The area shaped of vulcano procces. The result of the research indicates that : there were two categories level of suitability of areas for dragon fruit, very appropriate and appropiate. The unit of areas as very appropriate were the unit of areas M3.I.ENT.Qal.Kc, M6.I.ENT.Qal.Smk found in Ketaping village. The unit of areas M3.I.ENT.Qal.Tgl found in Tapakis Ulakan village. The unit of areas as appropriate were M6.I.ENT.Qal.Kc, M9.I.ENT.Qal.Pr, M9.I.ENT.Qal.Smk, F1.I.ENT.Qal.Pr, F1.I.ENT.Qal.Smk, found in Ketaping village. The unit of areas M9.I.ENT.Qal.Swh, M9.I.ENT.Qal.Tgl, F1.I.ENT.Qal.Swh, found in Ulakan village. The unit of area M9.I.ENT.Qal.Kc, found in Tapakis village. The unit of areas M3.I.ENT.Qal.Swh, M6.I.ENT.Qal.Swh, found in Sunua village. The unit of areas F1.I.ENT.Qal.Kc, F1.I.ENT.Qpt.Kc, F1.I.EPT.Qal.Kc found in Sungai Buluh village. The unit of areas V3.I.ENT.Qal.Kc, V3.I.EPT.Qal.Kc found in Kurai Taji village. The unit of area V3.I.EPT.Qal.Pr found in Padang Bintungan village. The unit of area V3.I.ENT.Qal.Swh found in Pauh Kamba village .The unit of area V3.I.EPT.Qal.Swh found in Kapalo Koto village.